Physical Activity as Medicine - How Regular Movement Shapes Cardiovascular, Metabolic, Mental, Musculoskeletal, and Cognitive Health - Lewalski, Tymon; Słuchocka, Joanna; Florczyk, Martyna; Lewalski, Oskar; Płuciennik, Lidia; Jeruć, Klaudia (Quality in Sport, 2026)
Physical activity is often discussed in the language of performance, body composition, or lifestyle, yet modern evidence shows that it also functions as a broad-spectrum medical intervention. The clinical importance of regular movement reaches far beyond calorie expenditure. Across population studies, randomized trials, and guideline documents, higher physical activity levels are linked to lower all-cause mortality, lower cardiovascular risk, reduced incidence of type 2 diabetes, better blood-pressure control, fewer depressive symptoms, better sleep, improved functional capacity in older age, and stronger musculoskeletal health [1-7]. The strongest relative gains are often seen when previously inactive people begin doing even modest amounts of activity, supporting the now familiar but still underused message that some activity is better than none [1,3].This article reviews the medical case for physical activity with a focus suitable for a high-quality sports newspaper: what physical activity is, how it affects the body, why it protects health across the life course, and how much is required to generate meaningful benefit. It also addresses limits and caveats. Exercise is not a magic shield, and benefit depends on dose, consistency, recovery, and context. Nonetheless, current evidence supports a simple conclusion: physical activity remains one of the most accessible, scalable, and cost-effective tools in modern medicine. In a world shaped by sedentary work, screen exposure, and chronic disease, movement is not merely training; it is treatment.